The age dependent change in the incidence of calcaneal spur - Ozan Beytemür; Mehmet Öncü (Acta Orthopaedica et Traumatologica Turcica, 2018)
Objective: The aim of the present study was to evaluate the association between the calcaneal spur incidence and age, gender and side. Methods: Lateral ankle X-rays of 1335 patients (550 (41.2%) females and 758 (58.8) males; mean age: 46.5 ± 13.5 years) who referred to our hospital because of trauma were reviewed. Incidence of plantar calcaneal spur, posterior calcaneal spur and association of such incidences with age, gender and side were all evaluated. Results: Incidences of plantar calcaneal spur and posterior calcaneal spur were detected as 32.2% (male: 31%, female: 34%) and 13.1% (male: 11%, female: 16%), respectively. Incidence of plantar calcaneal spur increased by age whereas there was not any association with gender and location. The highest incidence was detected as 41.8% over 70 years of age. Incidence of posterior calcaneal spur increased by age and female gender whereas no significant association was observed with location. The highest incidence was detected as 22.3% between 61 and 70 years of age. Conclusion: Incidences of plantar and posterior calcaneal spur were detected as 32.2% and 13.1%, respectively. Both plantar and posterior calcaneal spur incidence increases by age. Posterior calcaneal spur occurs significantly more frequently in females while, no difference is found between the males and females in incidence of the plantar calcaneal spur. Level of evidence: Level IV, diagnostic study. Keywords: Calcaneal spur, Heel spur, Bone spur, Incidence, Foot